Designing an (AI) Enhanced Training Program Based on Physical Level Using Performance Sensors to Develop Speed Endurance and Some Basic Skills for Young Football Players - Kwair, Ali Nadhim (Pubmedia Jurnal Pendidikan Olahraga, 2025)
Sport training no longer relies solely on coaches’ experience, intuition, and practice as it did in the past. Instead, it has become more advanced and precise, thanks to artificial intelligence (AI) technologies. In the digital era, athletes and coaches now have access to advanced analytical tools that enable them to assess performance with high levels of accuracy, surpassing traditional human capabilities. The research problem stems from the fact that many young players experience a decline in their performance during matches in the Iraqi league due to reduced speed endurance. This decline negatively impacts passing accuracy, decision-making speed, and the ability to excel in one-on-one situations. This issue prompted the researcher to design a training program using AI-enhanced performance sensors based on players’ physical levels to develop speed endurance and some fundamental football skills.